Nature and chemical abundances of a sample of Lyman-α emitter objects at high redshift - Dors, Oli L.; Agarwal, Bina; Rydberg, Claes-Erik (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We built a grid of photoionization models and compiled already available observational emission line intensities ($1000 \,\, \lt \,\, λ $(Å) &l
Gesehen am 24.05.2019